(untitled) (Journal of Energy and Safety Technology (JEST), 2026)
Hydrogen is increasingly recognized as a clean energy carrier and proton exchange membrane water electrolysis (PEMWE) has attracted significant attention as a pathway for green hydrogen production because of its ability to deliver high efficiency and rapid response. However, despite advancements in performance, the inherent safety aspects of PEMWE remain insufficiently addressed. Hydrogen is categorized under a wide flammability range, low ignition energy and risks of leakage, fire, explosion and corrosion that threaten its reliability. This project aims to identify and analyze potential hazards in PEMWE systems to evaluate their inherent safety level by using Heikkilä’s Inherent Safety Index (ISI) and proposing design improvements based on the principles of inherent safety: minimization, substitution, moderation and simplification. The study applied ISI scoring for both chemical and process hazards by evaluating factors such as hydrogen-oxygen mixing, flammability, explosiveness, corrosiveness, inventory, pressure and equipment complexity. Results showed PEM to fall within the medium hazard category with hydrogen-oxygen mixing and corrosion as key concerns. Design improvements were proposed based on the four principles such as reducing hydrogen inventory, using corrosion-resistant materials, operating at lower pressures and simplifying stack design. Based on the findings, it demonstrated that inherent safety assessment provides a pathway to enhance PEMWE reliability and align with hydrogen production with industrial safety standards and sustainability goals.